Are News Audiences Increasingly Fragmented? A Cross‐National Comparative Analysis of Cross‐Platform News Audience Fragmentation and Duplication. (25th July 2017) - Fletcher, Richard; Nielsen, Rasmus Kleis
Abstract : The move to high‐choice media environments has sparked fears over audience fragmentation. We analyze news audiences across media platforms (print, television, and online) in 6 countries, going beyond platform‐specific, single‐country studies. We find surprisingly high levels of news audience duplication, but also that cross‐platform audiences vary from country to country, with fragmentation higher in Denmark and the United Kingdom than in Spain and the United States. We find no support for the idea that online audiences are more fragmented than offline audiences, countering fears associated with audience segmentation and filter bubbles. Because all communication exists in the context of its audience, our analysis has implications across the field, underlining the importance of research into how trends play out in different contexts.